Kampanye Edukasi Telang di Beberapa Sekolah di Kota Ternate sebagai Instrumen Bahan Ajar - Rima Melati; Nurhasanah (Jurnal Pemberdayaan Masyarakat, 2022)
Conservation efforts of medicinal plants, such as butterfly pie in Ternate City should be a priority. The plant provides a historical meaning of the worldwide botanical nomenclature. Its population and utilization, however, start to vanish and disappear. The purpose of this activity is students familiar and its use of butterfly pie. Campaign and education about butterfly pie is carried out in three elementary schools and one senior high school in Ternate City that are located in Salero Village, Kasturian, Sangadji, and North Sangadji. The activity is implemented in several stages using different methods. The activity starts with a briefing, discussion for students of Kubermas, socialization, observation, campaign with extension methods, lectures, planting using a PRA method, mentoring in creating mini books. The activity’s output is teaching material instruments available at schools that consist of natural prop, which is plant in school yard and mini books available in the school library. Based on the results of final observation, butterfly pie have been planted in the schools and 100% of post activities. College students, and teachers know the plant from its botanical aspects and utilization and they agree if butterfly pie is appointed as a flora icon of Ternate Island.